The fundamentals of transport in living tissues quantified by medical imaging technologies - Hirsch, Sebastian; Schaeffter, Tobias; Sack, Ingolf (Springer International Publishing, 2018)
Physiology is the science of the mechanical, physical, bioelectrical, and biochemical functions of living systems. All physiological processes are based on physical and biochemical principles. Quantitative medical imaging exploits these principles to measure parameters of those processes noninvasively in vivo. Parameters measured by quantitative medical imaging have to be in agreement with values that would be obtained from standardized measurements from physics or material sciences, if these were applicable for living tissues. Technical advancements have led to the emergence of various methods for quantifying biophysical and constitutive tissue parameters. This chapter focuses on quantitative medical imaging of physiological processes that are related to different types of physical transport mechanisms. More specifically, we will show that continuity of mass and energy can be interpreted as overarching principles that govern seemingly unrelated modes of energy or mass transport. For this, the derived transport equations will be reviewed from the perspective of medical imaging modalities such as magnetic resonance imaging (MRI), positron emission tomography (PET), or ultrasound with a focus on water diffusion, blood perfusion, fluid flow, and mechanical wave propagation.
CRIS-Team Scopus Importer:2022-08-03